2013
DOI: 10.1016/j.ijid.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The significance of serum urokinase plasminogen activation receptor (suPAR) in the diagnosis and follow-up of febrile neutropenic patients with hematologic malignancies

Abstract: We conclude that suPAR is an important biomarker that can predict infections in the early stage of febrile neutropenia with high sensitivity and NPV for patients with hematologic malignancies. It is also advantageous since it shows the response to treatment with antibiotherapy in the early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, mean plasma suPAR levels in patients were significantly different from mean suPAR levels found in healthy controls (2.7 ng/ml) from time point ER onwards ( Figure 1A). The concentrations we found in samples from healthy controls were similar to those found in healthy controls in previous studies [17][18][19].…”
Section: Plasma Supar Concentrations After Traumasupporting
confidence: 90%
“…Furthermore, mean plasma suPAR levels in patients were significantly different from mean suPAR levels found in healthy controls (2.7 ng/ml) from time point ER onwards ( Figure 1A). The concentrations we found in samples from healthy controls were similar to those found in healthy controls in previous studies [17][18][19].…”
Section: Plasma Supar Concentrations After Traumasupporting
confidence: 90%
“…Although neutrophils appeared to represent the major source of suPAR in ICU patients in vivo, suPAR might be released from other cells, including non-circulating cells, as well. This would, for instance, explain why suPAR serum levels can be elevated in neutropenic patients with infections [42]. In fact, the cellular origin of suPAR may substantially differ in organ-specific disease settings, and such mechanisms may additionally contribute to circulating suPAR in ICU patients with organ failure(s).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 17 eligible studies, 9 studies including 1237 patients reported the usefulness of suPAR for diagnosing infections131415161718192021, and 10 studies including 3041 patients reported its usefulness for predicting mortality14212223242526272829. The characteristics of the studies are presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%